American masculine : stories - Ray, Shann (Graywolf Press, 2011)
The American West has long been a place where myth and legend have flourished. Where men stood tall and lived rough. But that West is no more. In its place Shann Ray finds washed up basketball players, businessmen hiding addictions, and women fighting the inexplicable violence that wells up in these men. A son struggles to accept his father's apologies after surviving a childhood of beatings. Two men seek empty basketball hoops on a snowy night, hoping to relive past glory. A bull rider skips town and rides herd on an unruly mob of passengers as he searches for a thief on a train threading through Montana's Rocky Mountains. In these stories, Ray grapples with the terrible hurt we inflict on those we love, and finds that reconciliation, if far off, is at least possible. .